Enhanced energy harvester performance by a tension annealed carbon nanotube yarn at extreme temperatures. Issue 43 (24th October 2022) - Hu, Xinghao; Bao, Xianfu; Wang, Jian; Zhou, Xiaoshuang; Hu, Hongwei; Wang, Luhua; Rajput, Shailendra; Zhang, Zhongqiang; Yuan, Ningyi; Cheng, Guanggui; Ding, Jianning
Abstract : Carbon nanotube (CNT) yarns generate electrical energy when they were stretched in an electrolyte, and they have been exploited for diverse applications such as self-powered sensors and human health monitoring systems. Abstract : Carbon nanotube (CNT) yarns generate electrical energy when they were stretched in an electrolyte, and they have been exploited for diverse applications such as self-powered sensors and human health monitoring systems. Here we improved the capacitance change and harvester performance of a coiled CNT yarn by using an incandescent tension annealing process (ITAP). When undergoing stretching cycles at 1 Hz, a coiled ITAP yarn can produce 2.5 times peak electrical power and 1.6 times output voltage than that of a neat CNT yarn. Electrochemical analysis shows that the capacitance of the ITAP yarn decreased by 20.4% when it was stretched to 30% strain. Microstructure results demonstrate that the large capacitance change may result from the densified electrochemical surface by the ITAP. Moreover, the potential of the zero charge (PZC) of ITAP yarns was shifted to a more negative value than that of the neat CNT yarn, which means that more charges were injected into the ITAP yarn once it was immersed in an electrolyte. Thus, the large capacitance change and initial injected charge are two main reasons for enhancing the harvester performance of the ITAP yarn. In addition, by annealing a twisted CNT yarn before it was coiled, we further increased the output peak power density to 170 W kg −1 at a strain of 55%.